Voltage-gated Sodium Channels: Structure, Function and Channelopathies (Handbook of Experimental Pharmacology,, 2018)
This book provides a timely state-of-the-art overview of voltage-gated sodium channels, their structure-function, their pharmacology and related diseases. Among the topics discussed are the structural basis of Na+ channel function, methodological advances in the study of Na+ channels, their pathophysiology and drugs and toxins interactions with these channels and their associated channelopathies.